Pengembangan Media Interaktif pada Pembelajaran Larutan Elektrolit dan Non Elektrolit untuk Siswa SMA Kelas X - Anita Herda; Muhammad Damris; Asrial Asrial (Universitas Jambi, 2014)
Macroscopic and symbolic representation used in chemistry instruction to represent chemical changes are unable to visualize chemical changes that occur at atomic and molecular level. The purpose of this study is to develop interactive multimedia to enhance of macroscopic and symbolic representation by providing submicroscopic representation of electrolyte and non electrolyte solutions. The media was developed by using Adobe Flash and validated by experts and used for trial in small and large groups of students before the final product was being used in a real classroom teaching based on Computer Model approach. Providing submicroscopic representation attracts student’s attentions and retention in studying the teaching materials and potentially improves student’s understanding and achievement.